Food fraud in the Alps? — Detection of chamois (Rupicapra rupicapra) in firm raw sausages, ham, and meat via qualitative duplex real-time PCR. (May 2021) - Derz, Wiebke; Pavlovic, Melanie; Huber, Ingrid; Schalch, Barbara; Gerdes, Lars
Abstract: Background: Firm raw sausages or ham from game species like chamois, red deer, or roe deer are typical meat products from the alpine regions in Germany, Italy, Austria, and Switzerland. Increased hunting effort and limited numbers make chamois meat more expensive than comparable game meat. In routine analysis at Bavarian Health and Food Safety Authority (LGL), screening of meat relevant animal species is usually performed by LCD array. However, chamois is not included on the commercial array. A simple alternative method for chamois detection in mixed products was therefore required. Results: We developed a duplex probe-based real-time PCR (duplex qPCR) that facilitates the specific detection of chamois and a universal eukaryotic gene as control, especially in processed meat products. Detection of chamois was sensitive (chamois DNA content of 1.25 pg/μL or 0.05% is detectable), robust (eight variations of PCR conditions tested), and specific (inclusivity and exclusivity). Detection of Eukarya in the duplex assay can be used both as an inhibition control, and as a rough estimation for the chamois content in the sample. We analysed 20 firm raw sausages with chamois as a declared ingredient. Eleven sausages were free of chamois meat, for three sausages, a ΔCq(Chamois-Eukarya) > 10 indicated the use of chamois meat as minor ingredient, and in six sausages, abundant amounts of chamois meat were detected. Furthermore, among three analysed chamois hams, one consisted of roe deer meat instead. Conclusions: The developed duplex qPCR is an easy to use tool to verify the presence of the declared ingredient chamois meat, especially in processed meats like sausages. The considerable proportion of products lacking declared chamois meat (55% or 11/20 for firm raw sausages, 33% or 1/3 for ham), indicates the need for further controls in this non-standard food segment. Highlights: Development of a qualitative duplex probe-based PCR for chamois detection. Food fraud involving chamois sausages and ham. Replacement of chamois meat by other venison.